Contamination of Agricultural Soils in Some Baghdad Areas with Antibiotics Resistant Pathogenic Fecal Bacteria - Fatima Kh. Dawood; Huda S. A. Al-Hayanni; Maitham A. Sultan (مجلة كلية الطب, 2023)
Background: Early studies have shown that agricultural soil contains various types of microorganisms, especially bacteria, including coliform bacteria (Salmonella, Shigella, Klebsiella, Escherichia coli, and Enterobacter) with fecal Gram-positive bacteria like Enterococcus faecalis. Therefore, the current study aimed to investigate the contamination of Iraqi agricultural soils with pathogenic fecal bacteria (Escherichia coli and Enterococcus faecalis) and study the antibiotic sensitivity patterns of soil-isolated bacteria because it is a dangerous indicator when transmitted to humans.